"Teacher factors as predictors of students' achievement in English language in Ibadan South-West Local Government Area,Oyo State, Nigeria " (2017)
English Language is a compulsory subject at all levels of education and a prerequisite for admission into higher institutions in Nigeria. However, students' achievement in the subject is poor. This underachievement has been attributed to some teacher factors, (attitude towards English teaching, teaching experience, teacher's content knowledge and text utilization). Previous studies focused largely on univariate influence of these factors without consideration of their composite and relative contribution to students' achievement. This study adopted a descriptive research survey design. Four research questions were raised and ten randomly selected public senior secondary school two students in Ibadan Southwest Local Government Area and two instruments were used to collect data. Data were analyzed using descriptive statistics and multiple regression at 0.05 level of significance. Findings revealed a significant relationship between teacher factors and students' achievement in English Language (R2 = 0.616, F (4,19) =0.431, p0.037). There were relative effects of the factors on students' achievement- teacher attitude (R2 = 0.808, F (4, 19) =0.242, p0.002), teaching experience (R2=0.536, F (4, 19) = 1.492, p0.031), teacher's content knowledge (R2 = 0.801, F (4, 19) = 1.335, p 0.041) and text utilization (R2 = 0.594, F (4, 19) = 0.209, p0.023) Teacher attitude was considered the factor that predicts students' achievement in English most. It is recommended that instructional materials should be provided for English Language teachers, they should be sponsored to workshops, seminars and conferences and their salaries should be paid promptly in order to improve on their attitude, content knowledge and text utilization.